Characteristics and Control of Low Temperature Combustion Engines Employing Gasoline, Ethanol and Methanol - Maurya, Rakesh Kumar (Mechanical Engineering Series, 2018)
This book deals with novel advanced engine combustion technologies having potential of high fuel conversion efficiency along with ultralow NOx and particulate matter (PM) emissions. It offers insight into advanced combustion modes for efficient utilization of gasoline like fuels. Fundamentals of various advanced low temperature combustion (LTC) systems such as HCCI, PCCI, PPC and RCCI engines and their fuel quality requirements are also discussed. Detailed performance, combustion and emissions characteristics of futuristic engine technologies such as PPC and RCCI employing conventional as well as alternative fuels are analyzed and discussed. Special emphasis is placed on soot particle number emission characterization, high load limiting constraints, and fuel effects on combustion characteristics in LTC engines. For closed loop combustion control of LTC engines, sensors, actuators and control strategies are also discussed. The book should prove useful to a broad audience, including graduate students, researchers, and professionals. Offers novel technologies for improved and efficient utilization of gasoline like fuels; Deals with most advanced and futuristic engine combustion modes such as PPC and RCCI; Comprehensible presentation of the performance, combustion and emissions characteristics of low temperature combustion (LTC) engines; Deals with closed loop combustion control of advanced LTC engines; State-of-the-art technology book that concisely summarizes the recent advancements in LTC technology.